2008
DOI: 10.1186/1471-2431-8-16
|View full text |Cite
|
Sign up to set email alerts
|

Anthropometric surrogates to identify low birth weight Nepalese newborns: a hospital-based study

Abstract: Background: In Nepal, more than 90% of the deliveries take place at home where birth weight is often not recorded. In developing countries, low birth weight (LBW, <2500 grams) accounts for 60-80% of neonatal deaths. Early identification and referral of LBW babies for extra essential newborn care is vital in preventing neonatal deaths. Studies carried out in different populations have suggested that the use of newborn anthropometric surrogates of birth weight may be a simple and reliable method to identify LBW … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

11
32
2
1

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 50 publications
(46 citation statements)
references
References 16 publications
11
32
2
1
Order By: Relevance
“…Decrease in LBW cases in 7 years time may also indicate improvement in health status of the country, awareness in people regarding antenatal care. Yet in another study 21 carried out in same city pokhara 3 years ago (2008) out of 400 newborns only 8.5% was found to be LBW, which is much lower than our fi ndings. This diff erence may be due to the fact that their study included only term babies whereas our study has included term as well as preterm babies.…”
Section: Discussioncontrasting
confidence: 84%
“…Decrease in LBW cases in 7 years time may also indicate improvement in health status of the country, awareness in people regarding antenatal care. Yet in another study 21 carried out in same city pokhara 3 years ago (2008) out of 400 newborns only 8.5% was found to be LBW, which is much lower than our fi ndings. This diff erence may be due to the fact that their study included only term babies whereas our study has included term as well as preterm babies.…”
Section: Discussioncontrasting
confidence: 84%
“…Maternal mean weight in that study 6 was 49.4 ± 6 kg and mean BMI was 21.31 kg/m 2 where as in this study at KMCTH, mean maternal weight was 59.73 ± 8.36 kg and maternal mean BMI was 25.37 ± 3.85 kg/m 2 showing a signifi cant increase in maternal nutrition within these 20 year period. A recent study done at the same hospital in 2010 by Aryal DR et al 15 also showed increased birth weight (mean birth weight was 3023 gms), which are depicted in Table 6 showing comparison among two hospitals in birth weight at 33 weeks, 36 weeks and 40 weeks respectively.…”
Section: Discussionsupporting
confidence: 57%
“…In developing countries, low birth weight (LBW) <2500 g accounts for 60-80% of neonatal deaths 2 . Neonatal anthropometric parameters are signifi cant predictive factors of neonatal morbidity and mortality.…”
mentioning
confidence: 99%
“…Studies are lacking in this particular area even though many studies are there showing correlation with birth weight. [4][5][6][7][8][9][10][11][12][13][14] We trialed the BMI cutoff points at 11, 12, 13 for the anthropometric surrogates and compared their efficacy as provided in Table 2. This was done with proof from other studies, where their mean BMI ranged from 11 to 13.…”
Section: Discussionmentioning
confidence: 99%
“…These studies showed that the Mid Arm circumference, Chest circumference and head circumference correlated well with birth weight. [4][5][6][7][8][9][10][11][12][13][14] A study done by Brock RS, charted BMI for newborns according to the gestational age and the mean BMI in term neonates were found to be 13.25±1.11. 15 It also validated BMI as a good tool for accessing nutrition.…”
Section: Introductionmentioning
confidence: 99%